(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The soybean cyst nematode (SCN) Heterodera glycines was found in three soybean fields near Pavia (ltaly) during the summer 2000. This quarantine nematode was not known in Italy. The soybean plants were smaller, with "yellow draft" disease, the roots were poorly developed and without or with few nitrogen nodules. The population of SCN found was well established, and all stages were recorded. Adult females and juveniles of H. glycines had high abundance. An average of 59.5 cysts for 100 cm3 soil were recorded disease. The density of population ranged from 7900 to 19200 SCN eggs/100 cm3 soil. This record highlights a probable permanent establishment of this plant parasitic nematode in North ltaly.